Consumer Issues in Health Services - Dr. Poornima Y (IJRDO - Journal of Applied Management Science, 2019)
Consumerism has been in existence since the beginning of Market Economy. But many consumers are not merely consumers, they are also producers of goods and services and so there should be a synergetic approach to the problem of consumer exploitation. Coming to the field of health, this approach becomes more significant. The producers of cosmetics, drugs and the health providers need to be persuaded to see that they don’t let down the consumer and doctors should always remember their Hippocratic Oath and see that the patient and the family will not become bankrupt in their run for medical help. Consumer awareness and producer realization are to be nurtured without fail for society’s health and survival. Some doctors say that they have paid lakhs and crores as donation for medical seats and have to recover that from patients. But what about the merit students who were educated at the expense of the society? There is no end to the argument. There appears a way to come out of this problem. A good medical insurance may temporarily solve the problem. No doubt consumers will be wise in investing medical insurance.